2021
DOI: 10.1021/acsaem.0c02841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pt and Ionomer Distribution on Polymer Electrolyte Fuel Cell Performance and Durability

Abstract: Carbon black (CB), which has been widely used as a catalyst support, has been treated by various activation processes in order to increase the surface area. High-surface-area CB has a high pore volume in the primary particles. The degree of ionomer impregnation in the nanosized pores is able to be evaluated by the hysteresis volume, which is calculated from N2-adsorption analysis. We investigated the effect of distributions of both Pt and ionomer on the surface of CB support nanopores on the cell performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 45 publications
2
77
1
Order By: Relevance
“…This finding indicates that the catalyst should have most of the active sites on the external surface to maintain good high current density performance, with a small fraction inside the pores for protection from the ionomer poisoning for high mass activity [106]. Further, Kaobayshi et al [95] determined that catalysts with large nanopore capacities can utilize Pt in pores at an intermediate current density. There is a reduction in Pt poisoning because the number of Pt NPs not in contact with the ionomer increases.…”
Section: Morphologymentioning
confidence: 98%
See 3 more Smart Citations
“…This finding indicates that the catalyst should have most of the active sites on the external surface to maintain good high current density performance, with a small fraction inside the pores for protection from the ionomer poisoning for high mass activity [106]. Further, Kaobayshi et al [95] determined that catalysts with large nanopore capacities can utilize Pt in pores at an intermediate current density. There is a reduction in Pt poisoning because the number of Pt NPs not in contact with the ionomer increases.…”
Section: Morphologymentioning
confidence: 98%
“…Another factor in electrocatalytic performance is the pore size of the material. Pore sizes are classified as macropores (>50 nm in diameter), mesopores (2-50 nm in diameter), and micropores (<2 nm in diameter) as shown in Figure 7 [95]. Mesopores are considered the most advantageous pore size because the ionomer cannot interact with the Pt particle inside micropores, essentially making them unavailable [95].…”
Section: Pore Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the kb support with accessible pores was found to show higher electrode reaction activity than that with curved pores. kobayashi et al reported that in the case of the KB support with large pores at the cathode, the Pt nanoparticles in the large pores showed a higher effective surface area and a higher electrode reaction activity than those on other sites [2].…”
Section: Introductionmentioning
confidence: 99%